Family Business Internationalization in Paradox: Effects of Socioemotional Wealth and Entrepreneurial Spirit - Jin, Chenfei; Wu, Bao; Hu, Yingjie (Frontiers in Psychology, 2021)
This study investigates the internationalization (i. e., foreign investment) of small family businesses by classifying the effects of external socioemotional wealth (family reputation) vs. internal socioemotional wealth (family involvement). The study involved 2,704 small family businesses in China, and the results support the hypothesis that family reputation has a positive effect on internationalization, while family involvement has a negative effect on internationalization. Moreover, entrepreneurial spirit reinforces the positive effect of family reputation on internationalization and enhances the negative relationship between family involvement and internationalization. This study contributes by examining the effect of entrepreneurial spirit as a potential balancing factor for the paradoxical influence of internal vs. external socioemotional wealth.